Status of ’akad nikah’ ownership of jointly acquired property between married couples according to Shariah perspective - Ahmad, Akli; Fisol, Wan Nazjmi Mohamed (Linguistics and Culture Review, 2021)
’Akad nikah’ is a ’syar’ie contract’ which binds married relationships as a bond that stipulates some of the rights that their spouses must fulfill either physical and inner maintenance (nafkah) of a wife. The ruling of this maintenance is obligatory to be adorned according to the rates and conditions set by syara’. However, the maintenance rate varies between an individual and another. It is based on the individual capabilities of the giver and the individual position of the recipient. Some maintenance rates are referring to the ’urf of a place. The obligatory nafkah given to the spouse is the absolute possession of the recipient without being withdrawn by the giver. While every gift other than mandatory maintenance is included in the category (tabarru’) or a donation that is permissible or required. This type of grant will specify the occurrence of transfer if the recipient has already received it in cash (qabadh). While the jointly acquired property is essentially any property that is jointly owned by two or more parties, by sharing the capital for its ownership.